Public Awareness in Efforts to Defend The Country in The Digital Era in Order to Fight Hoaxes to Maintain State Resilience - Ida Bagus Kade Ary Dwipayana; Made Irvan Sastra Abenk; Nur Haliza Lukman (Catuspata, 2022)
In this era of very rapid technological development, people certainly have felt the convenience of technology, teenagers in Indonesia themselves use technology a lot to communicate and find information. Every citizen has their respective rights and obligations in maintaining the integrity of the nation, but in reality at this time awareness in defending the country has not been able to be implemented. The attitude of defending the country must be owned by every citizen, seeing from the increasingly advanced digital era it has brought several negative impacts on the resilience of the country. The sense of defending the country is not only the responsibility of the TNI or the police, but the responsibility of every citizen. One form of non-defence of the state that often occurs in Indonesia is the spread of hoaxes. The spread of hoaxes is very fast in cyberspace because Indonesian people like things that are viral that make them curious. How to find out hoax news well, hoax news titles contain incitement, from unclear sources, and others. This can have a positive impact and we as a society are expected to make the best use of increasingly advanced technology. In addition, a new innovation and creativity is needed that can make it easier for people to understand the importance of defending the country.